2002
DOI: 10.1210/en.2002-220173
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Tumorigenesis in Prolactin Gene-Disrupted Mice

Abstract: Targeted disruption [knockout (KO)] of the mouse prolactin (PRL) gene created an animal model of primary isolated PRL deficiency in which there is no detectable PRL bioactivity. Pituitary glands of young adult female PRLKO mice were hyperplastic, and many cells had expanded cytoplasms with granular accumulations of an N-terminal peptide encoded by the disrupted PRL gene (KO/10 peptide). Confocal imaging showed that the pituitaries in PRL(+/+) and PRL(+/-) females contained dense accumulations of apparently Gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 37 publications
0
14
0
1
Order By: Relevance
“…Loss of the inhibitory effect of hypothalamic dopamine release due to tumoral ''stalk section effect'' was suggested as a likely etiology [15]. Investigations on transgenic mice [40] confirm the existence of this mechanism. The association of lactotroph hyperplasia and prolactinoma is known to occur in humans as well [41].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the inhibitory effect of hypothalamic dopamine release due to tumoral ''stalk section effect'' was suggested as a likely etiology [15]. Investigations on transgenic mice [40] confirm the existence of this mechanism. The association of lactotroph hyperplasia and prolactinoma is known to occur in humans as well [41].…”
Section: Discussionmentioning
confidence: 99%
“…Also, their actions on the lactotropes in the presence of pituitary mesenchymal variant folliculo-stellate cells have not been tested. Additionally, overexpression of many of these factors using a transgenic approach have resulted only in hyperplasia, and they resulted in adenoma formation only in old age and/or only in females, suggesting that endogenous estrogens are a requirement [59][60][61]. Therefore, the role of these growth factors in the mechanisms leading to tumorigenesis could not be critically evaluated.…”
Section: Xenoestrogen-treated Ratsmentioning
confidence: 99%
“…Since D2R KO mice develop hyperprolactinemia, pituitary hyperplasia and, finally, pituitary adenomas, it was suggested that both the lack of dopamine inhibition and stimulation of cell proliferation induced by high circulating levels of PRL were responsible for the anterior pituitary cell growth observed in these mice [79]. However, it was later observed that PRL KO [80] and PRLR KO [81] mice also exhibited anterior pituitary hyperplasia. It was concluded that activation of PRLR signaling was not involved in promoting pituitary adenoma formation.…”
Section: Prolactin Actions In the Pituitarymentioning
confidence: 99%